Considerations about the Precedent - Taruffo, Michele (2016)
In this article, the author tells us about the precedent along with its characteristics, as well as its role in the law. He tells us, also, about the situation of a precedent ruled by an International Court and its implications in the domestic law of each country. Likewise, he defines what is not a precedent and points us how effective is in the Law. Finally, he points us about the particularity and the universalism in the precedents, then he gave us his final thought of this theme.